Influence of Herbicide Safeners on Creeping Bentgrass (Agrostis stolonifera) Tolerance to Herbicides. (September 2015) - Elmore, Matthew T.; Brosnan, James T.; Armel, Gregory R.; Vargas, Jose J.; Breeden, Gregory K.
Abstract : Glasshouse research was conducted to investigate the efficacy of herbicide safeners for improving creeping bentgrass (CBG) tolerance to various herbicides. CBG injury from amicarbazone (150 g ha −1 ), bispyribac-sodium (110 g ha −1 ), fenoxaprop-p-ethyl (35 g ha −1 ), imazapic (45 g ha −1 ), quinclorac (1, 050 g ha −1 ), or topramezone (37 g ha −1 ) applied in combination with the herbicide safeners naphthalic anhydride or isoxadifen-ethyl was evaluated. These safeners reduced CBG injury from topramezone only. Topramezone was then applied in combination with naphthalic anhydride, isoxadifen-ethyl, cloquintocet-mexyl (cloquintocet), fenchlorazole-ethyl, mefenpyr-diethyl, and benoxacor. These experiments determined that CBG injury was lowest from topramezone in combination with cloquintocet. Additional experiments evaluated topramezone (37 g ha −1 ) with several rates of cloquintocet and determined that applications at ≥ 28 g ha −1 reduced CBG injury similarly. Cloquintocet (28 g ha −1 ) increased topramezone I50 values against CBG, but not large crabgrass or goosegrass. The cytochrome P450 (cP450) inhibitor malathion (1000 g ha −1 ) reduced topramezone I50 values against CBG in one experimental run. Topramezone–cloquintocet combinations warrant further research in field settings.